Dyadic patterns of mental health and quality of life change in partners and patients during three months of cardiac rehabilitation - Bouchard, Karen; Gareau, Alexandre; McKee, Katya; Lalande, Kathleen; Greenman, Paul S; Tulloch, Heather (Journal of family psychology, 2023)
The effects of mental health on quality of life (QoL) over the course of a couple's recovery from a patient's cardiac event are unknown as partner outcomes are rarely considered within cardiac rehabilitation. To capture the transactional nature of recovery from a cardiac event, this research investigated the link between longitudinal changes in the mental health of couples in which at least one of the partners had cardiac disease and changes in their QoL during cardiac rehabilitation. Participants (N = 184 dyads) completed questionnaires measuring anxiety, depression, and QoL at baseline (enrollment) and 3 months (discharge). Dyadic data were analyzed using the Actor-Partner Interdependence Model with integrated latent change scores. The results indicated that improved anxiety was associated with significant positive changes in physical and emotional QoL for both the patient and partner (actor effects). A reduction in depression in both partners from baseline to follow-up predicted an increase in emotional QoL for patients and partners, and an increase in physical QoL for partners (actor effects). Patients whose depression decreased from enrollment to the completion of cardiac rehabilitation were associated with partners' greater positive changes in emotional QoL than were patients whose depression did not decrease, and reductions in partners' anxiety over time predicted positive changes in patients' physical QoL (partner effects). Findings underscore the need to screen for and attend to patients' and partners' mental health outcomes postcardiac event, as positive changes in mental health symptoms may optimize changes in patients' and partners' emotional and physical QoL. (PsycInfo Database Record (c) 2023 APA, all rights reserved).The effects of mental health on quality of life (QoL) over the course of a couple's recovery from a patient's cardiac event are unknown as partner outcomes are rarely considered within cardiac rehabilitation. To capture the transactional nature of recovery from a cardiac event, this research investigated the link between longitudinal changes in the mental health of couples in which at least one of the partners had cardiac disease and changes in their QoL during cardiac rehabilitation. Participants (N = 184 dyads) completed questionnaires measuring anxiety, depression, and QoL at baseline (enrollment) and 3 months (discharge). Dyadic data were analyzed using the Actor-Partner Interdependence Model with integrated latent change scores. The results indicated that improved anxiety was associated with significant positive changes in physical and emotional QoL for both the patient and partner (actor effects). A reduction in depression in both partners from baseline to follow-up predicted an increase in emotional QoL for patients and partners, and an increase in physical QoL for partners (actor effects). Patients whose depression decreased from enrollment to the completion of cardiac rehabilitation were associated with partners' greater positive changes in emotional QoL than were patients whose depression did not decrease, and reductions in partners' anxiety over time predicted positive changes in patients' physical QoL (partner effects). Findings underscore the need to screen for and attend to patients' and partners' mental health outcomes postcardiac event, as positive changes in mental health symptoms may optimize changes in patients' and partners' emotional and physical QoL. (PsycInfo Database Record (c) 2023 APA, all rights reserved).